Abstract labour theory of value and theory of price (2013)
The renewal of Marx's interpretation of capitalist society implies the recovery and development of his Theory of Value. The stream of thought known as Abstract Labour Theory of Value, or New Interpretation, proposes to do this, and points out that value is a category that is formed in the interaction between production and circulation (and not just in production, as the Ricardian conception). The theory of value exceeds a theory of price, but requires this piece of analysis that for now is underdeveloped. This paper aims to contribute to the task of constructing a price theory compatible with the abstract labor theory of value, and approaches this task in a simple commodity economy scheme.